Does Accounting Conservatism Reduce Overpricing Caused by Short‐Sales Constraints? - Mashruwala, Christina; Mashruwala, Shamin (Contemporary Accounting Research, 2018)
ABSTRACT Prior research documents that, in the presence of investor disagreement, short‐sales constraints can lead to equity overvaluation. We examine whether conservative accounting practices reduce the susceptibility to such overpricing, as predicted by Miller (1980). Consistent with Miller's prediction, we find that when shorting constraints and disagreement are high, the degree of overvaluation decreases systematically with accounting conservatism. These findings suggest that financial reporting conservatism helps improve market efficiency by counteracting the tendency to overvaluation that typically occurs in the presence of short‐selling constraints and divergence of opinion.